Alkyl-dependent self-assembly of the first red-emitting zwitterionic Cu4I6 clusters from [alkyl-P(2-Py)3]+ salts and CuI: when size matters. Issue 7 (3rd January 2019) - Artem'ev, Alexander V.; Pritchina, Elena A.; Rakhmanova, Marianna I.; Gritsan, Nina P.; Bagryanskaya, Irina Yu.; Malysheva, Svetlana F.; Belogorlova, Nataliya A.
Abstract : First examples of zwitterionic CuI-based complexes showing red photoluminescence are reported. Abstract : A series of red-emissive Cu4 I6 clusters have been synthesized from alkyl-tris(2-pyridyl)phosphonium halides, [R-PPy3 ]Hal, and CuI. The size of the alkyl substituent (R) has a dramatic impact on the structure of the clusters assembled. [Me-PPy3 ]I salt reacts with CuI (1 : 2) to give the ionic [Cu(Me-PPy3 )I]2 Cu2 I4 complex consisting of the scorpionate [Cu( N, N ′, N ′′-Me-PPy3 )I] + cation. Under similar conditions, [Pr-PPy3 ]I forms the zwitterionic [Cu4 I6 (Pr-TPP)2 ] complex containing an unusual stepwise [Cu4 I6 ] cluster core. The use of [Bu-PPy3 ]I or [Bn-PPy3 ]I in this reaction leads to zwitterionic [Cu4 I6 (R-TPP)2 ] complexes, in which a linear-shaped [Cu4 I6 ] module appears. Photophysical studies supported by TD-DFT computations have revealed that the title complexes in the solid state at 298 K exhibit a red photoluminescence ( λ emmax = 620–650 nm) with short lifetimes (0.04–2.10 μs), which are assigned to the thermally activated delayed fluorescence (TADF) mixed with the cluster centered ( 3 CC) phosphorescence. The compounds synthesized are the first red-emitting representatives of the recently discovered family of zwitterionic CuI-based complexes (so-called "AIO" structures).